Letters to Florence O'Donoghue from various individuals (K - L) in response to queries and newspaper advertisements seeking information on Liam Lynch - O'Donoghue, Florence, 1895-1967 (1941)
Correspondents are Tadg Kearney, James Kelly, Donal Kiely, Jim Killian, James Kirwan, Robert Langford, Siobhán Langford, Tom Laurence, James Leahy and John Lehane.
Keywords: O'Donoghue, Florence, -- 1895-1967 -- Correspondence; Lynch, Liam, -- 1893-1923; Irish Republican Army; Ireland -- History -- 1910-1921; Ireland -- History -- 1922-